The Evolution and Impact of Traditional Library Digitalization (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The transformation of traditional libraries into digital knowledge hubs has redefined the way information is accessed, stored, and utilized. This review explores the process of digitalization in libraries and examines its far-reaching implications for users, librarians, and institutions alike. The shift has enhanced accessibility, streamlined information retrieval, and supported remote learning and research. However, challenges related to digital divides, preservation integrity, and data privacy persist. This article critically reviews current trends, technologies, benefits, and drawbacks of digitalizing library collections, drawing on academic literature, case studies, and institutional experiences. The paper concludes with future directions for libraries in an increasingly digital world.